Developing Power Point Interactive Media to Teach Speaking Skill For 11th Grade Students SMK Islam 1 Blitar - Yaqin, Moh. Ainul; Makrifah, Istinatul; Saifuddin, Ahmad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
English is the most widely spoken language worldwide. According to the Ministry of Education and Culture in 1981, the Indonesian government has determined that English is the first foreign language spoken in Indonesia since it is crucial for the advancement of science, technology, and culture as well as for fostering international cooperation. This research development model uses Research and Development (R&D). Research result the implementation of media development that has been carried out by class XI TKJ SMK Islam 1 Blitar has eight stages in product development according to needs. At the development stage, Observation of potential problems, data collection, product design, design validation, design revision, design trial, product revision and trial use are carried out. This is done so that the Power Point Interactive media used is suitable for use.